Advance in Polymer Composites: Fire Protection and Thermal Management (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint collates the latest advances in polymer composites, including research on various aspects related to fire protection, flame retardancy, thermal stability, and thermal management. Through the introduction and discussion in this reprint, readers will gain a comprehensive understanding of the importance of fire protection and thermal management in polymer-based materials and their significant impact on society. We expect that this reprint will inform and inspire researchers, engineers, and students in related fields and promote further research and applications in this area.